Life cycle assessment of organic photovoltaic charger use in Europe: the role of product use intensity and irradiation. (1st October 2019) - Glogic, Edis; Weyand, Steffi; Tsang, Michael P.; Young, Steven B.; Schebek, Liselotte; Sonnemann, Guido
Abstract : Solar chargers for mobile phones are the first integration of organic photovoltaic (OPV) technology into commercial products. Although environmental impacts of OPVs have been studied extensively, the performance of chargers have been narrowly examined in reference to intensity of their use and use geographies. To explore these aspects, we study the environmental impacts of OPV chargers considering the charger as a substitute for a local electricity grid supply for charging a mobile phone. A consequential life-cycle assessment (LCA) was carried out to evaluate the environmental performance of the OPV charger in six European countries representative of different electricity grids and solar irradiation contexts. Particular effort is made to explore the implications of use intensity of the charger and determine a frequency at which charger is competitive. The results suggest that using an OPV charger has the potential to be environmentally friendly only in countries with high fossil-fuel share in their electricity supplies. The OPV charger is environmentally beneficial in Greece and Spain across most of the evaluated impact categories if used 100–120 times per year, which is practical given the high solar insulation in the two countries. Charging a phone with OPV in Germany or the Netherlands is environmentally-friendly only under conditions of intensive use of the device, or for selective impact categories. In the category of climate change, charging with OPV would represent an improvement in Greece and Germany. In two countries a phone-charging supported by OPV generates 2.5 kg of CO2 -equivalents per year in comparison to 2.9–3 kg CO2 -equivalents charging from the grid. Phone-charging supported by OPV in Norway and France is more impactful than using the grid for the majority of impact categories, including the category of climate change. The study contributes a novel methodology for looking at photovoltaic technology and helps inform users and policymakers who should consider the local context before an adoption of environmental technologies. Graphical abstract: Image 1 Highlights: An OPV charger is compared with electricity grid for charging a mobile phone. Charger impacts are considered in view of its use intensity and solar irradiation. The charger has potential to be eco-friendly in four of six investigated countries. Improvements in water-related categories are traded for higher impacts to the air.